The Impact of the Development of Trade Practices on Enforcement of International Environmental Law - Birkah Latif; Syamsuddin Muhammad Noor; Juajir Sumardi; Irwansyah Irwansyah (Sriwijaya Law Review, 2019)
The issue of trade and environment is always debatable. Degradation and damaging to the environment surge the countries in making comprehensive and multi-approach planning. This is based on the view that trade should not only count for profit but also carry out calculations and planning for the impacts and conditions when the business is carried out and after completion. The purpose of this paper is to find out whether the environment causes trade not to be carried out and to end economic growth and there is a solution to balance the environment and trade as prevention in both fields through environmental protection legal instruments. The first issue showed that trade that used to be a source of income that is the main target of countries, nevertheless, the unwise planning and also corrupt cases has made the trade become the trigger for environmental damage. This condition caused by a lack of awareness in law enforcement and even various corruption issues causing trade to become a threat, especially for the environment. The second issue arises, which is the mechanism in balancing trade and the environment to preserve the environment and encourage the country's economic growth by optimizing the implementation of environmental protection laws. This paper uses normative legal research methods by collecting data derived from the literature, legislation, articles, and cases that occur within countries. The result shows that more states and stakeholder using more technique on achieving a balance of trade and environment protection, with a pro-environment calculation, it is expected that trade will be carried out in parallel with environmental preservation.